2017
DOI: 10.3390/toxins9070231
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin Prevalence throughout Lentic Waterbodies in Coastal Southern California

Abstract: Toxin producing cyanobacterial blooms have increased globally in recent decades in both frequency and intensity. Despite the recognition of this growing risk, the extent and magnitude of cyanobacterial blooms and cyanotoxin prevalence is poorly characterized in the heavily populated region of southern California. Recent assessments of lentic waterbodies (depressional wetlands, lakes, reservoirs and coastal lagoons) determined the prevalence of microcystins and, in some cases, additional cyanotoxins. Microcysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 75 publications
2
33
1
Order By: Relevance
“…The recognition of harmful genera and occasionally toxins in streams [32], lakes/lentic water bodies [30,33], and rivers [33] that lead to the coast prompted this coordinated sampling effort at the land-sea interface. The objectives were to identify potential toxin-producing cyanobacterial taxa and to determine if specified cyanotoxins were present in detectable quantities within these brackish water ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of harmful genera and occasionally toxins in streams [32], lakes/lentic water bodies [30,33], and rivers [33] that lead to the coast prompted this coordinated sampling effort at the land-sea interface. The objectives were to identify potential toxin-producing cyanobacterial taxa and to determine if specified cyanotoxins were present in detectable quantities within these brackish water ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…CyanoHABs may consist of multiple forms of toxins, but limited data is currently available on where and when toxins co-occur and under what environmental conditions [ 47 , 65 , 66 , 67 ]. To our knowledge, this study is unique in providing a year-round and multi-year record that allows the confirmation of the presence and co-occurrence of four cyanotoxins (dissolved MCY, CYN, ANA and BMAA) in a US freshwater body ( Table 2 and Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relatively high magnitude of MC (200 µg/L) and ethanol (~300 mg/L) concentrations that were employed in this study were selected to represent worst case bloom conditions. Past sampling of lakes and reservoirs throughout the United States (U.S.) has indicated that concentrations of total MC rarely exceed 200 µg/L [78][79][80][81][82][83][84], whereas total dissolved organic carbon (DOC) concentrations ranged from 0.2 to 516 mg/L [40]. It is important to note a considerable portion of the readily bioavailable fraction of the total DOC pool may be attributed to secreted algal organic matter, especially in HAB impacted environments [38,39].…”
Section: Discussionmentioning
confidence: 99%